If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2h + 12 = 68 Reorder the terms: 12 + 2h = 68 Solving 12 + 2h = 68 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 2h = 68 + -12 Combine like terms: 12 + -12 = 0 0 + 2h = 68 + -12 2h = 68 + -12 Combine like terms: 68 + -12 = 56 2h = 56 Divide each side by '2'. h = 28 Simplifying h = 28
| 4(2-b)=12 | | 11(2x)+7x=870 | | -4(8+3m)-8=-(6m-2) | | (x-4)2=25 | | -7x-2x+10x+3x=48 | | 5.25-6.75= | | 41n(x+7)=20 | | 9y^2-2x+7=0 | | 8(-0.25+0.25c)-2c=-2 | | 4y-2-2y=10 | | 15-24a=30 | | 4(2.5+1.75b)+7b=10 | | -4p=.667 | | 20=12+4x | | 15.3s=14.2s-18.92 | | 10-2x=2+x | | 5.25-x=-1.5 | | 2x-3+4k=39 | | 4x-67=153-6x | | 87.75=p*0.045*3 | | log(x+2)=2.3 | | 4+0.1b=6 | | 7(p+2)-3=-1+3p | | 6b-2c=18 | | -12.19+8.6k=8.7k-11.9 | | 2520=180m-360 | | -39-3x=65+5x | | 8a-2c=-2 | | 0=-4x^2+9x+5 | | 1/2x+7=10.75 | | 4(x+4)+14=-2x | | 0.5x^2-3x=0 |